Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Help …....image attached

Help …....image attached

Question Image
Grade:12

1 Answers

Jitender Singh IIT Delhi
askIITians Faculty 158 Points
6 years ago
Hello student,
Please find answer to your question
ycos(x) + xcos(y) = \pi
y(0)cos(0) + 0.cos(y) = \pi
y(0) = \pi
Differentiate
y'cos(x) -ysin(x) + cos(y) -xsin(y)y' = 0
y'(0)cos(0) -y(0)sin(0) + cos(y(0)) -0.sin(y(0))y'(0) = 0
y'(0)cos(0) + cos(\pi ) = 0
y'(0) = 1
y'(cos(x) -xsin(y)) = ysin(x) - cos(y)
Differentiate
y''(cos(x) -xsin(y)) + y'(-sin(x)-sin(y)-xcos(y)y') = y'sin(x)+ycos(x) - sin(y)y'y''(0)(cos(0) -0.sin(y(0))) + y'(0)(-sin(0)-sin(y(0))-0.cos(y)y') = y'sin(0)+y(0)cos(0) - sin(y(0))y'(0)y''(0) = y(0)
y''(0) = \pi

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free